The causes of wars and other essays - Howard, Michael (Cambridge Harvard University Press, 1983)
Public consciousness of the threat of nuclear war is rising steadily. Responses to the nuclear dilemma are conflicting and often confusing. Never have we been more in need of information and perspective, for if we wish to avoid war we must understand it. Michael Howard offers an analysis of our present predicament by discussing those issues that cause war and make peace. His book includes an examination of nuclear strategy today, views of the past about the conduct of international relations, ethics, modes of defense, and studies of military thinkers and leaders. The Causes of Wars illuminates the interrelationship between men and ideas, between war and other social forces, and between our present situation and its roots in the past.
Reprint of works originally published 1962-1982.
Keywords: War